Characterization of Ag:Ni Nano Particles Produced by Pulse Nd:YAG laser - Naama, Ahmed Abd Al-Razza (Iraqi Journal of Science, 2022)
This work presents the characteristics of plasma produced by fundamental wavelength (1064 nm) Q- switched Nd:YAG laser on Ag:Ni alloy in distilled water were investigated at different laser energies by optical emission spectroscopy technique. The size of produced nanoparticles from Ag:Ni target in distilled water were studied, by x-ray diffraction, UV-visible absorbance and atomic force microscopy, at different laser energies. Spectroscopic measurements show that electron temperature and electron density increase with increasing laser energy. It was found from AFM measurements that the produced nanoparticle size decrease from 97.13 nm to 71.20 nm, while XRD shows that the crestalline size decrease from 15.5 nm to 9 nm with increasing pulse laser energy. UV- visible absorbance shows at plasmon peaks shifted from 410 to 395 nm with increasing laser energy.